A Rare Side Effect due to TNF-Alpha Blocking Agent: Acute Pleuropericarditis with Adalimumab - Hakan Ozkan; Ahmet Seckin Cetinkaya; Tekin Yildiz; Tahsin Bozat (Case Reports in Rheumatology)
Tumor necrosis factor-alpha antagonism is an important treatment strategy in patients with rheumatoid arthritis, psoriatic arthritis, vasculitis, and ankylosing spondylitis. Adalimumab is one of the well-known tumor necrosis factor-alpha blocking agents. There are several side effects reported in patients with adalimumab therapy. Cardiac side effects of adalimumab are rare. Only a few cardiac side effects were reported. A 61-year-old man treated with adalimumab for the last 6 months due to psoriatic arthritis presented with typically acute pleuropericarditis. Chest X-ray and echocardiography demonstrated marked pericardial effusion. Patient was successfully evaluated for the etiology of acute pleuro-pericarditis. Every etiology was excluded except the usage of adalimumab. Adalimumab was discontinued, and patient was treated with 1200 mg of ibuprofen daily. Control chest X-ray and echocardiography after three weeks demonstrated complete resolution of both pleural and pericardial effusions. This case clearly demonstrated the acute onset of pericarditis with adalimumab usage. Acute pericarditis and pericardial effusion should be kept in mind in patients with adalimumab treatment.